Landmarks to Identify Petrous Apex Through Endonasal Approach Without Transgression of Sinus - Negm, Hazem M.; Singh, Harminder; Dhandapani, Sivashanmugam; Cohen, Salomon; Anand, Vijay K.; Schwartz, Theodore H. (Journal of Neurological Surgery Part B: Skull Base, 2018)
Objectives The use of nasopharyngeal landmarks to localize the petrous apex has not been previously described. We describe a purely endoscopic endonasal corridor to localize the petrous apex without transgressing any of the paranasal sinuses.Methods Anatomical dissections of four formalin preserved cadaveric heads (eight petrous apices) were performed to evaluate the feasibility of a nonsinus-based approach and illustrate the surgical landmarks and measurements that are useful for surgery in this area.Results The Eustachian tubes, fossa of Rosenmüller (FR), and posterior end of the middle and inferior turbinates are constant landmarks, which can be identified without opening any nasal sinuses. The petrous apex is located on an extended straight line connecting the upper end of the torus tubarius (TT) and the roof of the FR. The distance from upper end of TT to the roof of FR measured 9.875 (±0.99) mm, and the distance from roof of the FR to the petrous apex measured 9.75 (±1) mm.Conclusion With well-defined landmarks, the inferior, medial petrous apex can be reached using the endoscopic endonasal approach without crossing the sinus cavities.
Keywords: endoscopic endonasal approach; petrous apex; torus tubarius; fossa of Rosenmüller